Writing 21st century fiction [ high-impact techniques for exceptional storytelling - Maass, Donald (Cincinnati, Ohio : Writer's Digest Books, 2012)
Strong combination of examples, techniques, and exercises. Practical tools in each chapter allow novelists to apply these methods immediately to create fiction that transcends genre, creates realities unique to its authors, conjures characters who feel more "real" than real people, and shows readers the world around them in new ways
1. 21st century fiction -- 2. The death of genre -- 3. The inner journey -- 4. The outer journey -- 5. Standout characters -- 6. The three levels of story -- 7. Beautifully written -- 8. The 21st century novelist -- 9. The elements of awe
Includes index
Keywords: Authorship; Authorship -- Technique; Creative writing; Fiction -- Technique